Do hedonic price indexes change history? The case of electrification - Harald Edquist (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
Rapid price decreases for ICT-products in the 1990s have been largely attributed to the introduction of hedonic price indexes. Would hedonic price indexing also have large effects on measured price and productivity during earlier technological breakthroughs? This paper investigates the impact of hedonic and matched model methods on historical data for electric motors in Sweden 1900-35. The results show that during the productivity boom of the 1920s, current prices for electric motors decreased by 13.2 and 12.2 percent per year depending on whether hedonic or matched model price indexes were used. This indicates high productivity growth in the industry producing electric motors in 1920-29. In contrast to Sweden, the US annual total factor productivity growth was only, according to current best estimates, 3.5 percent in Electric machinery compared to 5.3 percent in manufacturing in 1920-29. However, hedonic price indexes were not used to calculate US productivity. Finally, it is shown that the price decreases for electric motors in the 1920s were not on par with the price decreases for ICT-equipment in the 1990s, even if hedonic indexing is used in both cases.
Keywords: L60; N60; O10; O14; O33; O40; 330; Hedonic price index; Electric motor; Productivity growth; Electrification; ICT revolution; Productivity growth; General Purpose Technologies; Innovation; Hedonischer Preisindex; Preisindex; Motor; Produktivität; Informationstechnik; Schweden; Indexberechnung